Pemberdayaan Masyarakat Nelayan Di Desa Sejahtera Kecamatan Sukadana Kabupaten Kayong Utara - Sikwan, Agus (Tanjungpura University, 2020)
The title of this research is: “The Empowerment Program Model of the Poor Society in Sungai Raya Subdistrict which at Bengkayang Regency of West Borneo Province”. Background overshadow by writer desire to lay open until where program the Economic Empowerment of Coastal area Society (EECS) especially to fisherman Society which has been programmed by ambulatory Regency Government. Internal issue formulation this research is “What will be implementation process program the Economic Empowerment of Coastal area Society (EECS) at Sungai Raya Sub-district, Regency Bengkayang ? Research Type use qualitative and technique of data collecting use the in-depth interview and observation. While data analysis uses descriptive analysis. Program EECS at Sungai Raya Subdistrict of Regency Bengkayang to in the implementation of since the year 2007 is not re-continued. This matter because of some problems and factor influencing its implementation, so that program the EECS 2007 is even transferred to Regency area/other Subdistrict. Therefore, need the correct stages: steps and quickly in handling it, is good the then Government of Regency of Bengkayang and also institution or institute which have the competence of so that program EECS earn the implementation and re-continued because very needed by fisherman society especially in Sungai Raya Subdistrict.